Demographic and Household Characteristics Related to Childhood Obesity in Public Elementary Schools in Penjaringan - Yoseveline Christiani; Robi Irawan; Yunisa Astiarani (Faculty of Public Health, Sriwijaya University, 2021)
Indonesia is experiencing the rise of childhood obesity prevalence, and the majority profound in low socioeconomic areas, which may aggravate the harmful impacts on the children's growth and health. This study was conducted to find significant factors of childhood obesity in low socioeconomic areas. A cross-sectional study design was carried out at two public elementary schools in Penjaringan subdistrict, North Jakarta. All students in both schools participated in the study and were selected based on inclusion criteria. A total of 731 students (grades 1 to 6) were eligible. The nutritional status was assessed by trained staff by calculating the Body Mass Index (BMI) for age and classifying the outcome based on the WHO z-scores chart. Parents filled a demographic and socioeconomic questionnaire to collect children's birthdate, parents' educational level, employment status, income, and health insurance. Logistic regression was performed to evaluate the association. The prevalence of obesity among students was 13.41%. The regression showed that male and younger students were likely to be obese. The students whose mothers were in secondary level of education, have an unemployed father, or in the low-income family (p<0.05) were more likely to be obese. The study shows that male and younger students were associated with childhood obesity. Besides, educated mothers, unemployed fathers, and families with low income tend to have obese children. The school needs to have a specific program for male and younger age students to increase healthy habits. Nutrition assessment, recommendation, and parents' involvement in school-based health programs need to be enhanced.